2020
DOI: 10.1007/s13300-020-00983-y
|View full text |Cite
|
Sign up to set email alerts
|

A Consideration of the Psychological Aspects to Managing Patients with Painful Diabetic Neuropathy: An Insight into Pain Management Services at a Tertiary Centre in the UK

Abstract: Painful diabetic neuropathy (pDN) is characterised by both sensory and affective disturbances, suggesting a complex bidirectional relationship of neuropathic pain and mood disorders. Data on pDN indicate that neuropathic pain reduces quality of life, including mood and physical and social functioning. Depression and pain coping strategies such as catastrophising and social support predict pain severity. There is a significant and reciprocal relationship between depressed mood and increased pain. The key featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
1
0
2
Order By: Relevance
“…Si bien las recomendaciones hechas en el país para la rehabilitación del paciente con DM consideran solamente la rehabilitación tras la amputación de pies, hay otras áreas de rehabilitación que subrayan la importancia de la atención psicológica, como la disminución de la capacidad visual debido a la retinopatía diabética (Cooper et al, 2020), el dolor neuropático (Twiddt et al, 2021) e incluso las enfermedades periodontales (Malekmahmoodi et al, 2020). Por último, la atención a personas que están próximas a la cirugía se enfoca en la evaluación y seguimiento psicológico para asegurar que los resultados obtenidos del procedimiento quirúrgico se mantengan el mayor tiempo posible (Galli et al, 2018).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Si bien las recomendaciones hechas en el país para la rehabilitación del paciente con DM consideran solamente la rehabilitación tras la amputación de pies, hay otras áreas de rehabilitación que subrayan la importancia de la atención psicológica, como la disminución de la capacidad visual debido a la retinopatía diabética (Cooper et al, 2020), el dolor neuropático (Twiddt et al, 2021) e incluso las enfermedades periodontales (Malekmahmoodi et al, 2020). Por último, la atención a personas que están próximas a la cirugía se enfoca en la evaluación y seguimiento psicológico para asegurar que los resultados obtenidos del procedimiento quirúrgico se mantengan el mayor tiempo posible (Galli et al, 2018).…”
Section: Discussionunclassified
“…Aparte de las amputaciones, hay distintas complicaciones diabéticas que requieren de un trabajo de rehabilitación por las afectaciones físicas y psicológicas que provocan en el funcionamiento diario de los pacientes. La neuropatía diabética implica una intensa labor de rehabilitación debido a la experiencia del dolor constante causado por el daño nervioso, lo que afecta el bienestar físico y psicológico del paciente (Twiddt et al, 2021). Las intervenciones cognitivo-conductuales para el manejo de la sintomatología depresiva, la ansiedad, los trastornos del sueño y los pensamientos catastróficos han mostrado buenos resultados para aminorar la experiencia del dolor (Kioskli et al, 2019).…”
Section: Atención Psicológica Para La Rehabilitación De Personas Con Dmunclassified
“…In patients with comorbid psychological distress, psychological therapy can be utilised. 80 Examples of psychological therapy include cognitive behavioural therapy (CBT), behavioural therapy, and acceptance and commitment therapy (ACT). 81 An RCT pilot study assessing the use of CBT in patients with PDPN demonstrated significant decreases in pain severity and intensity in participants who received CBT versus treatment as usual.…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%
“…It generates serious consequences all over the world. It has a huge impact on the human physiology as well as cognitive, psychological and social functioning [2][3][4][5]. Diabetes has a vast societal and economic cost in terms of increased medical expenses, lost productivity and premature death, and intangible costs such as lower quality of life in many populations [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%